Improved spectroscopic parameters and rotational energy structure of the ground vibrational state of AsH3 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Bekhtereva E. S. Elena Sergeevna; Gromova O. V. Olga Vasilievna; Sidko S. S. Sergey Sergeevich; Sydow Ch. Christian; Bauerekker (Bauerecker} Z. Kh. Zigurd Khermann (2025, 2025)
Title screen